Политическое участие: теория, методология и измерение с применением метода шкалограммирования по Гуттману - Клюенко, Э. (Социология: теория, методы, маркетинг, 2005)
The article is devoted to the analysis of theory, methodology and measuring of political participation. The author comparatively scrutinized theoretical problems of genesis, functions, role, and prognosis for the future of this phenomenon in the sociological theory in order to define the difference and commons in the existing approaches. Crucial analysis and generalizations of various political participation conceptions as well as empirical researches are offered to be correctly applied for the studying in the transitional society. The definition of political participation, its structure, motivation, main forms and factors, models of stratification in modern conceptions has been comparatively analyzed and systematized as a methodological base of empirical research. The author elaborated and tested the approach to assessment of political participation based on using Guttman’s one-dimensional continuity scale. Due to the approach, with presented reliability and validity, index of political participation (IPP) was calculated and four-dimensional model of political participation stratification was formed according to polling empirical data.